PERNIKAHAN DINI (Suatu Kajian Perilaku Menyimpang di Kanagarian Limau Gadang Lumpo Timur Kecamatan Iv Jurai Kabupaten Pesisir Selatan) - Sari, Helga Riantika; Kasih, Fitria; Jarudin, Jarudin (Bimbingan dan Konseling, 2014)
The reseach based on the phenomena of early married of adolescence, adolescence was labil age, the emotional was not stabil and low self control, as a result, there was fighting that refers to deviant behavior in early married that make suscatible to divorce. Purpose of this research to describe; 1) Behavioral form digress that happened at early married couple, 2) Behavioral cause digress that happened at early married couple. This research type is descriptive qualitative. This research was executed with method interview and observation with main informan Â 2 early married couple and 2 supporter informants were the parents of early married couple at Kanagarian Limau Gadang Lumpo Timur Kecamatan IV Jurai Kabupaten Pesisir Selatan. This data was tested by triangulat data, afterwards analysed with three phase 1) Data discount 2) Presentation of data 3) Withdrawal of conclusion. Of analysis result of research obtained has finding that behavioral form digress that done by early married couple was household violence and does not the nun of responsibility and rights as wife husband properly. This matter because of this couple have emotion which not yet stabilized and also the lack of selfcontrol and adjustment of xself in nuptials so that often happened behavior and quarel digress in household.